Software process improvement assesment for multimodel environment tool to diagnose an organization [Evaluación de mejora de procesos software para entornos multi-modelo Herramienta para el diagnóstico de una organización] (2017)
Organizations that implement improvement processes to develop quality software usually appeal to SCAMPl-like evaluation methods in order to diagnose, plan and certify themselves. However, nowadays there is a need that goes beyond the evaluation, and it is the need to diagnose the processes maturity of the software development organizations that use more than one process improvement model or standard, i.e. a multi-model environment. lmplementing a multi-model environment for software process improvement is not an easy task since it demands the harmonization of models or standards with dissimilar structures, hence diagnosing the maturity of an organization that defines and implements a multi-model environment it not an easy task either. This work depicts a software tool to accomplish a diagnostic of an organization that uses or pretends to define a software process improvement multi-model environment that includes both traditional and agile models and standards. Such diagnostic determines the processes maturity level of an organization and allows us to define a methodology for recommending tools and techniques for software process improvement. © 2017 AISTI.